Combining several indicators to assess the effectiveness of tailor-made health plans in pig farms - Levallois, Pierre; Leblanc-Maridor, Mily; Scollo, Annalisa; Ferrari, Paolo; Belloc, Catherine; Fourichon, Christine (Peer Community Journal)

(untitled)
A tailor-made health plan is a set of recommendations for a farmer to achieve and maintain a high health and welfare status. Tailored to each farm, it is intended to be an effective way of triggering change. This study aimed to assess the effectiveness of tailor-made health plans in pig farms, designed in various situations after a systematic biosecurity and herd health audit. An intervention study was carried out in 20 farrow-to-finish pig farms. An initial standardized audit and discussion between the farm veterinarian and the farmer resulted in a specific plan. Compliance with recommendations was monitored during 8 months. Changes in health, performances and antimicrobial use were monitored. We defined two categories of plans: i) 14 plans targeting a given health disorder present in a farm; ii) 17 plans to improve prevention, not targeting a specific health disorder (a farm could have both types of plans). A small number of priority recommendations were made per farm. In 18 farms, farmers implemented 1 to 4 recommendations (none in 2 farms). Of the 17 non-disorder-specific plans, 11 were considered effective (>50% recommendations implemented), 3 intermediate (at least one but less than half of the recommendations implemented) and 3 ineffective (no implementation). Of the 14 disorder-specific plans, 9 were followed with full or good compliance (>50% recommendations implemented), 2 with intermediate compliance (1 recommendation implemented out of 2) and 3 with no compliance (no recommendation implemented). When at least one recommendation was implemented, change in clinical, performance and antimicrobial use indicators was assessed if a biological association with the disorder was deemed plausible and if their initial value showed room for improvement. Improvement was evidenced 4/9, 1/6 and 1/6 times for these indicators, respectively. Independently, veterinarians concluded that 8/14 plans were effective. Overall, tailor-made health plans were effective in triggering changes in farm management. Three key points were identified for future assessments of the effectiveness of tailor-made health plans. Compliance should be the first indicator of assessment. Outcome indicators and their monitoring periods should be adapted to each farm and to the targeted health disorder. Indicators should be combined to have a holistic description of the evolution of a health disorder. Further research is needed to identify how to select indicators to combine and how to combine them, according to health disorders.